2008
DOI: 10.1016/j.taap.2008.06.006
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression profiles modulated by the human carcinogen aristolochic acid I in human cancer cells and their dependence on TP53

Abstract: Aristolochic acid (AA) is the causative agent of urothelial tumours associated with aristolochic acid nephropathy. These tumours contain TP53 mutations and over-express TP53. We compared transcriptional and translational responses of two isogenic HCT116 cell lines, one expressing TP53 (p53-WT) and the other with this gene knocked out (p53-null), to treatment with aristolochic acid I (AAI) (50−100 µM) for 6−48 h. Modulation of 118 genes was observed in p53-WT cells and 123 genes in p53-null cells. Some genes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
7
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 88 publications
(136 reference statements)
9
47
7
1
Order By: Relevance
“…CDKN1A mediates the p53-dependent cell cycle G1 phase arrest in response to a variety of stress signals, including genotoxic stress, hypoxia, and oncogene activation. Our results were opposite to those reported (35) in p53-null cells after a 48-h exposure to AA (100 μM) in HCT 116 cell line. Previous data from Chang (33) showed that AA mixture (AAM; 41% AA I, 56% AA II) can cause arrest in the G0/G1 phase (from 37.6 to 49.2%) in human urinary tract epithelium cells (SV-HUC-1), suggesting that AA-induced cell cycle arrest at the G0/G1 phase is associated with cyclin E/cdk2 complex (the cdk inhibitor).…”
Section: ------------------------------------------------------------contrasting
confidence: 99%
See 2 more Smart Citations
“…CDKN1A mediates the p53-dependent cell cycle G1 phase arrest in response to a variety of stress signals, including genotoxic stress, hypoxia, and oncogene activation. Our results were opposite to those reported (35) in p53-null cells after a 48-h exposure to AA (100 μM) in HCT 116 cell line. Previous data from Chang (33) showed that AA mixture (AAM; 41% AA I, 56% AA II) can cause arrest in the G0/G1 phase (from 37.6 to 49.2%) in human urinary tract epithelium cells (SV-HUC-1), suggesting that AA-induced cell cycle arrest at the G0/G1 phase is associated with cyclin E/cdk2 complex (the cdk inhibitor).…”
Section: ------------------------------------------------------------contrasting
confidence: 99%
“…Several studies showed that AA can induce cytotoxic effects in human colon cancer HCT 116 cells, porcine renal LLC-PK1 cells, and opossum kidney (OK) cell line. The HK-2 cells used in our study were more sensitive to the cytotoxicity of AA than HCT 116 cells (35), and OK cells (40). The IC 50 of 24 h AA treatment for HK-2 cells and HCT 116 cells was 30 and 100 μM, respectively.…”
Section: ------------------------------------------------------------mentioning
confidence: 74%
See 1 more Smart Citation
“…The IC 50 values of AA after 24 h treatment in HK-2 cells and HCT 116 cells were 30 μmol/L and 100 μmol/L, respectively. Moreover, the effect of AA on gene expression was more profound in HK-2 cells than in HCT 116 cells [27] . A previous report indicated no significant difference in TP53 expression in P53-WT HCT 116 cells after a 24 h exposure to AA (100 μmol/L), whereas our study showed a marked downregulation of TP53 gene expression (fold change -1.92 after qRT-PCR confirmation) in 10 μmol/L AA-treated HK-2 cells (data not shown).…”
Section: Wwwchinapharcom Chen Yy Et Almentioning
confidence: 91%
“…In this in vitro study on the gene expression profiles of AA-treated (HK-2) cells, the normal human proximal tubular cell line was used, in contrast with the human colorectal cancer cell line (HCT 116) used by Simoes [27] . Our results showed that HK-2 cells were more sensitive to AA-induced cytotoxicity than HCT 116 cells.…”
Section: Wwwchinapharcom Chen Yy Et Almentioning
confidence: 99%